Variation in inherent Fo level differences between vowels as a function of position in the utterance and in the stress group - Reinholt Petersen, Niels (Annual Report of the Institute of Phonetics University of Copenhagen, 1979)
The inherent Fo level differences in the vowels u and ɑ were examined in a material which made it possible to vary the position of the vowels in the utterance, keeping their position in the stress group constant, and vice versa. The main finding was that the inherent Fo level differences were statistically significant in both stressed and unstressed syllables throughout the material, but in stressed vowels the differences were larger than in the unstressed ones. The effect of position in the utterance and stress group can be summarized as follows: In vowels in stressed position the differences tend to decrease through the utterance, in vowels in first posttonic position they (surprisingly) increase, and in second posttonic position they do not seem to vary systematically with the position in the utterance. Apart from the differences being larger in stressed than in unstressed syllables, there seems to be no effect in the unstressed vowels from their position in the stress group.